Annual cycles in the interstellar scintillation time-scales of PKSB1519-273 and PKSB1622-253 - Carter, S.; Ellingsen, S.; Macquart, Jean-Pierre; Lovell, J. (Wiley-Blackwell Publishing Ltd., 2009)
We have used the University of Tasmania's 30-m radio telescope at Ceduna in South Australia to regularly monitor the flux density of a number of southern blazars. We report the detection of an annual cycle in the variability time-scale of the centimetre radio emission of PKSB1622-253. Observations of PKS B1519-273 over a period of nearly 2 yr confirm the presence of an annual cycle in the variability time-scale in that source. These observations prove that interstellar scintillation is the principal cause of inter-day variability at radio wavelengths in these sources. The best-fitting annual cycle model for both sources implies a high degree of anisotropy in the scattering screen and that it has a large velocity offset with respect to the local standard of rest. This is consistent with a greater screen distance for these 'slow' intra-day variability(IDV) sources than for rapid scintillators such as PKS B0405-385 or J1819+3845.